The Role of Sexting on the Perception of Image-Based Sexual Abuse - Rollero, Chiara (Journal of interpersonal violence, 2023)
Gender-based violence is a widespread phenomenon that significantly impacts many women around the world. Among the different forms that it might take, image-based sexual abuse represents one of the most common forms nowadays. According to the literature, sexting—the sharing of sexually explicit messages or images—is one of the most important risk factors for image-based sexual abuse because sexts can be forwarded or published without the authorization of the originator. Nevertheless, sexting can play a role in sexual and relational development and serve as a first step in experimenting with sexual contact in real life. In this study (N = 603 from the general population), we examined the relations between people’s beliefs about sexting, attitudes toward it, and sexting behavior on the one hand, and reactions to a situation of nonconsensual dissemination of sexts on the other hand. Results showed that social pressure exerted by peers and partners to sext was associated with both positive attitudes toward sexting and sexting behaviors. Attitudes toward sexting, then, have a spillover effect on the reactions toward a victim of nonconsensual dissemination of sexts, in terms of empathy, victim blaming, and affective reactions. Implications for both research and policymaking regarding this form of gender-based violence are discussed.